Optimal system design for energy communities in multi-family buildings: the case of the German Tenant Electricity Law. (1st January 2022) - Braeuer, Fritz; Kleinebrahm, Max; Naber, Elias; Scheller, Fabian; McKenna, Russell
Abstract: Involving residential actors in the energy transition is crucial for its success. Local energy generation, consumption and trading are identified as desirable forms of involvement, especially in energy communities. The potentials for energy communities in the residential building stock are high but are largely untapped in multi-family buildings. In many countries, rapidly evolving legal frameworks aim at overcoming related barriers, e.g. ownership structures, principal–agent problems and system complexity. But academic literature is scarce regarding the techno-economic and environmental implications of such complex frameworks. This paper develops a mixed-integer linear program (MILP) optimisation model for assessing the implementation of multi-energy systems in an energy community in multi-family buildings with a special distinction between investor and user; the model is applied to the German Tenant Electricity Law. Based on hourly demands from appliances, heating and electric vehicles, the optimal energy system layout and dispatch are determined. The results contain a rich set of performance indicators that demonstrate how the legal framework affects the technologies' interdependencies and economic viability of energy communities with multi-energy systems. Certain economic technology combinations may fail to support national emissions mitigation goals and lead to lock-ins in Europe's largest residential building stock. The subsidies do not lead to the utilisation of a battery storage. Despite this, self-sufficiency ratios of more than 90% are observable for systems with combined heat and power plants and heat pumps. Social C O 2 mitigation costs range between 147.5–272.8 € / t CO 2 . Finally, the results show the strong influence of the heat demand on the system layout. Highlights: System optimisation of distinct operators and consumers in multi-family buildings. Inclusion of Tenant Electricity Law leads to complex investment and dispatch decisions. Highest profitability combining photovoltaic, combined heat and power and heat pump. Combined heat and power is favoured, but profits depend on building's heating demand. Legislation incentivises energy communities but may offset national CO2 mitigation.